1996
DOI: 10.1007/bf00022848
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for nitrogen use efficiency in winter wheat (Triticum aestivum L.)

Abstract: The new European Common Agricultural Policy and environmental considerations are certainly to change agricultural practices toward low input cultivation systems . Nitrogen is one of the main inputs of winter wheat in northern France and it contributes highly to phreatic water pollution . A research programme has then been set up in order to study whether it is possible to breed for winter wheat cultivars using more efficiently N fertilisers . Less nitrogen would be applied, decreasing pollution risks and opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 5 publications
(3 reference statements)
0
6
2
2
Order By: Relevance
“…In addition, the poor use of supplied N may lead to insufficient N availability for plants at times of peak demand with consequent yield reduction. Genotypes show different behaviour with different levels of available N across sites and growing seasons (Le Gouis and Pluchard 1996;Gallais and Coque 2005;An et al 2006). The two main components of NUE, N uptake efficiency and N utilisation efficiency, should both be taken into account to optimise NUE in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the poor use of supplied N may lead to insufficient N availability for plants at times of peak demand with consequent yield reduction. Genotypes show different behaviour with different levels of available N across sites and growing seasons (Le Gouis and Pluchard 1996;Gallais and Coque 2005;An et al 2006). The two main components of NUE, N uptake efficiency and N utilisation efficiency, should both be taken into account to optimise NUE in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Different morphophysiological characteristics, associated with both the uptake capacity (NUpE; defined here as a proportion of total N uptake to N availability in the soil) and efficiency of nitrogen utilization in grain mass formation (NUtE; defined here as the grain mass formed per unit of N absorbed), appear to be critical components of NUE (Moll et al 1982;Huggins and Pan 2003). Although numerous reports on genotypic variation in components of N efficiency already suggest potential applications of this genetic knowledge for wheat improvements (Dhugga and Waines 1989;Le Gouis and Pluchard 1996;Ortiz-Monasterio et al 1997;El Bassam 1998;Le Gouis et al 2000;Oracka et al 2000;Górny et al 2006a;Laperche et al 2006a;Kichey et al 2007;Baresel et al 2008;Barraclough et al 2010), relatively fewer attempts have been made to breed wheat for these traits (Van Ginkel et al 2001;Brancourt-Hulmel et al 2005;Löschenberger et al 2008;Wolfe et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Heterosis for N use efficiency however has rarely been investigated in detail. Le Gouis & Pluchard (1996) and Le Gouis et al (2002) found greater N capture in hybrids with greater grain and biomass yields, but nitrogen utilization efficiency was not explicitly presented and its physiology with relation to heterosis was not explored.…”
Section: Introductionmentioning
confidence: 99%